Enhanced neural phase locking through audio-tactile stimulation - Jagt, Mels; Ganis, Francesco; Serafin, Stefania (Frontiers in Neuroscience, 2024)
Numerous studies have underscored the close relationship between the auditory and vibrotactile modality. For instance, in the peripheral structures of both modalities, afferent nerve fibers synchronize their activity to the external sensory stimulus, thereby providing a temporal code linked to pitch processing. The Frequency Following Response is a neurological measure that captures this phase locking activity in response to auditory stimuli. In our study, we investigated whether this neural signal is influenced by the simultaneous presentation of a vibrotactile stimulus. Accordingly, our findings revealed a significant increase in phase locking to the fundamental frequency of a speech stimulus, while no such effects were observed at harmonic frequencies. Since phase locking to the fundamental frequency has been associated with pitch perceptual capabilities, our results suggests that audio-tactile stimulation might improve pitch perception in human subjects.